Going-concern initial public offerings - Willenborg, Michael; McKeown, James C. (Journal of Accounting and Economics, 2000)
We study the relation between audit reports and the capital-raising activities of small business by studying the role of going-concern (GC) audit opinions in IPOs. After controlling for other effects, we find that the presence of a GC opinion is positively related to whether a stock delists (for deleterious reasons) within two years of IPO. We also find that GC IPOs suffer less first-day underpricing. Based on Rock (1986), this implies that firms with GCs have less ex ante uncertainty in the sense that the information conveyed by a GC helps uninformed investors estimate the dispersion of secondary market values.